JOGGING AND PNF STRETCHING AGAINST CHANGES IN FLEXIBILITY - Y. Touvan Juni Samodra; Isti Dwi Puspita Wati; Maharani Fatima Gandasari; Ghana Firsta Yosika; Putra Sastaman B; Davi Sofyan (Journal Physical Education, Health and Recreation, 2023)
The problem in this study was to test and find out flexibility in students before and after carrying out the Dynamic stretching and PNF tests, so this study aimed to determine the effect of Dynamic stretching and PNF exercises on flexibility in students. This research was an experimental data analysis technique from Dynamic stretching exercises and PNF. The research instrument used the Sit and Reach tool. The samples in the study were from Tanjungpura University PKO students, class of 2022. The research instrument used was the Sit and Reached tool to find out flexibility which will be tested. After doing Dynamic stretching and PNF, this study concluded that Dynamic stretching and PNF exercises affected increasing flexibility before and after carrying out the stretching test, known as the Sit and Reach. From the data obtained, it was proven that after the trial test carried out the Dynamic stretching and PNF, there was an increase in flexibility values before and after the test was carried out.